Translationally controlled tumor protein interacts with connexin 43 and facilitates intercellular coupling between cardiomyocytes - Hu, Yaopeng; Cai, Wenqian; Hidaka, Yuko; Hiraishi, Keizo; Cang, Jiehui; Umemura, Masanari; Yokoyama, Utako; Knollmann, Björn C.; Ishikawa, Yoshihiro; Fujita, Takayuki (Frontiers in Cell and Developmental Biology, 2025)
IntroductionConnexins are gap junction proteins that play pivotal roles in intercellular communication. Connexin 43 (Cx43) is one of the most ubiquitously expressed connexin isoforms in human. Cx43 has been demonstrated to be involved in the pathological process of various diseases, including arrhythmias. Recently, translationally controlled tumor protein (TCTP), a highly conserved anti-apoptotic protein, has been shown to play an important role in protecting against the development of heart failure. However, its role in arrhythmogenesis remains unclear. In this study, we aimed to examine the interaction between TCTP and Cx43 and investigate the roles of TCTP in the formation of Cx43 gap junction channels and gap junctional intercellular communication (GJIC) in cardiomyocytes.Methods and resultsWe found that TCTP was predominantly expressed in the intercalated discs of mouse heart tissue. Cx43 in adult mouse hearts was coimmunoprecipitated using a TCTP-specific antibody. Additionally, co-localization of TCTP and Cx43 was demonstrated using a proximity ligation assay in iPS cell-derived human cardiomyocytes. TCTP silencing reduced the formation of Cx43 gap junction channels at the intercellular contacts between cardiomyocytes. Moreover, TCTP silencing significantly attenuated GJIC among cardiomyocytes. Interestingly, the development of ventricular arrhythmia was attenuated in cardiomyocyte-specific TCTP-overexpressing mice.ConclusionThese findings indicate that TCTP regulates GJIC. Thus, TCTP may be a therapeutic target for preventing Cx43-related pathogenesis.